Does a 2.5-year self-management education and support intervention change patterns of healthcare use in African-American adults with Type 2 diabetes? - Yeung, R. O.; Oh, M.; Tang, T. S. (Diabetic medicine, 2014)
Aims To investigate the impact of a 2.5‐year diabetes self‐management education and support intervention on healthcare use and to examine factors associated with patterns of healthcare use. Methods We recruited 60 African‐American adults with Type 2 diabetes who completed a 2.5‐year empowerment‐based diabetes self‐management education and support intervention. Primary healthcare use outcomes included acute care visits, non‐acute care visits and days lost to disability. Acute care was a composite score calculated from the frequency of urgent care visits, emergency department visits and hospitalizations. Non‐acute care measured the frequency of scheduled outpatient visits. To examine change in patterns of healthcare use, we compared the frequency of healthcare visits over the 6‐month period preceding the intervention with that in the last 6 months of the intervention. Results No significant changes in patterns of healthcare use were found for acute care, non‐acute care or days lost to disability. Multiple regression models found higher levels of depression (P = 0.001) to be associated with a greater number of non‐acute healthcare visits, and found longer duration of diabetes (P = 0.019) and lower levels of diastolic blood pressure (P = 0.025) to be associated with fewer days lost to disability. Conclusions Participation in a long‐term diabetes self‐management education and support intervention had no impact on healthcare use in our sample of African‐American subjects. What's new? This is one of only two studies examining healthcare use as an outcome of a long‐term self‐management education and a support intervention targeting African‐American adults with Type 2 diabetes. Participation in a 2.5‐year diabetes self‐management education and support intervention has no impact on acute care visits, non‐acute care visits or days lost to disability. Depressive symptomatology is a significant predictor of non‐acute healthcare use. Duration of diabetes and diastolic blood pressure are significant predictors of days lost to diabetes‐related disability.